Epidemiology of atypical parkinsonian syndromes - Raymond Y Lo (Tzu Chi Medical Journal)
Atypical parkinsonism or atypical parkinsonian syndromes (APS) refer to a group of neurodegenerative disorders which mimic typical Parkinson's disease but poorly respond to levodopa treatment and deteriorate faster. APS are very rare and among them, progressive supranuclear palsy (PSP), multiple system atrophy (MSA), and corticobasal degeneration (CBD) are the three relatively better characterized entities. The prevalence estimates of PSP, MSA, or CBD are mostly <10/105, and the incidence estimates are around 1/105 person-year; both estimates remain stable over the past few decades. The age at onset is relatively young for MSA at late 50s, followed by CBD at early 60s, and then PSP at late 60s. The gender difference is not significant in APS, although slight female predominance in CBD has been reported in literature. Little is known about genetic and environmental risk factors for PSP, MSA, and CBD; although the COQ2 mutation has been identified as a genetic risk for MSA, familial cases are extremely rare. Survival after symptom onset is generally within 10 years, but cases with longer disease duration do exist. Respiratory infection remains the major cause of death for APS, but cardiac arrest should be particularly considered in MSA. In addition to disease rarity, the phenotype–pathology discrepancy in APS makes the epidemiological studies even more challenging. Including biomarkers in future diagnostic criteria and establishing disease registry for collecting sufficient number of APS cases may increase the likelihood of finding modifiable risk factors for prevention and intervention.